Performance in Sound-Symbol Learning Predicts Reading Performance 3 Years Later - Horbach, Josefine; Weber, Kathrin; Opolony, Felicitas; Scharke, Wolfgang; Radach, Ralph; Heim, Stefan; Günther, Thomas (Frontiers in Psychology, 2018)
To master the task of reading, children need to acquire a coding system representing speech as a sequence of visual symbols. Recent research suggested that performance in the processing of artificial script that relies on the association of sound and symbol may be associated with reading skill. The current longitudinal study examined the predictive value of a preschool sound-symbol learning paradigm (SSP) of reading performance three years later. The Morse-like SSP, IQ, and letter knowledge (LK) was assessed in young preschool children. Reading outcome measures were examined three years later. Word reading, pseudoword reading, and reading comprehension was predicted with age, IQ, LK, and SSP. The results showed that SSP substantially predicted reading fluency and reading comprehension three years later. For reading fluency measures, the influence of further predictor variables was not significant and SSP served as a sole predictor. Reading comprehension was best explained by SSP and age. The amount of variance SSP explained in reading three years later was remarkably high, with an explained variance between 63 % and 82 %, depending on the outcome reading variable. SSP turned out to be a substantial predictor of later reading performance in a language with statistically reliable spelling-to-sound relations. As LK is highly dependent on educational support, we assume that children in our socioeconomically diverse sample did not have much opportunity to acquire letter knowledge in their home environment. In contrast, the SSP challenges students to acquire new spelling-to-sound relations, simulating a core aspect of natural reading acquisition. Future work will test this paradigm in less transparent languages like English and explore its potential as a future standard assessment in the study of early reading development.